Functionalized Graphene Quantum Dot Modification of Yolk–Shell NiO Microspheres for Superior Lithium Storage - Yin, Xiaojie; Chen, Hengqiao; Zhi, Chuanwei; Sun, Weiwei; Lv, Li‐Ping; Wang, Yong (Small (Weinheim an der Bergstrasse, Germany), 2018)
Yolk–shell NiO microspheres are modified by two types of functionalized graphene quantum dots (denoted as NiO/GQDs) via a facile solvothermal treatment. The modification of GQDs on the surface of NiO greatly boosts the stability of the NiO/GQD electrode during long‐term cycling. Specifically, the NiO with carboxyl‐functionalized GQDs (NiO/GQDsCOOH) exhibits better performances than NiO with amino‐functionalized GQDs (NiO/GQDsNH2). It delivers a capacity of ≈1081 mAh g−1 (NiO contribution: ≈1182 mAh g−1) after 250 cycles at 0.1 A g−1. In comparison, NiO/GQDsNH2 electrode holds ≈834 mAh g−1 of capacity, while the bald NiO exhibits an obvious decline in capacity with ≈396 mAh g−1 retained after cycling. Except for the yolk–shell and mesoporous merits, the superior performances of the NiO/GQD electrode are mainly ascribed to the assistance of GQDs. The GQD modification can support as a buffer alleviating the volume change, improve the electronic conductivity, and act as a reservoir for electrolytes to facilitate the transportation of Li+. Moreover, the enrichment of carboxyl/amino groups on GQDs can further donate more active sites for the diffusion of Li+ and facilitate the electrochemical redox kinetics of the electrode, thus together leading to the superior lithium storage performance. Metal–organic frameworks–derived yolk–shell NiO microspheres are modified by two types of functionalized graphene quantum dots (NiO/GQDs) via a facile solvothermal treatment. The modification of GQDs on the surface of NiO greatly boosts the stability of the NiO/GQD electrode with a superior lithium storage performance during long‐term cycling.